Recent Advances on Synthesis and Potential Applications of Carbon Quantum Dots - Magesh, Vasanth; Sundramoorthy, Ashok K.; Ganapathy, Dhanraj (Frontiers in Materials, 2022)
Fluorescent carbon nanoparticles also termed as carbon quantum dots (CQDs) have attracted so much interest when compared to the traditional semiconductor quantum dots due to their applications in chemical sensing, biomedical imaging, nanotechnology, photovoltaics, light-emitting diodes (LEDs) and electrochemistry. Along with their optical features, CQDs have desired properties such as less toxicity, environmentally friendly nature, inexpensive, and simple preparation processes. Also, CQDs can have their physical and chemical properties controlled by surface passivation and functionalization. This article provides an account of CQDs because of their distinct characteristics and considerable capacity in diverse applications. The article is categorized into various sections that highlighted various synthesis methodologies of CQDs with their advantages/disadvantages and their potential applications in sensors, bio-imaging, drug delivery, solar cells and supercapacitors. The different applications of CQD can be demonstrated by controlled synthesis methods. We have also discussed gas sensing applications of CQDs briefly and provided a brief overview of osmotic power generation using CQDs for energy applications.